2014
DOI: 10.1371/journal.pone.0106935
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Diabetic Peripheral Neuropathy in a Saudi Arabic Population: A Cross-Sectional Study

Abstract: The purpose of this cross-sectional study was to investigate the prevalence and correlates of diabetic peripheral neuropathy (DPN) in a Saudi population. The study population consisted of 552 diabetic participants with an average age of 53.4 years. Among this population, 62.7% were male and 94.9% had type 2 diabetes. The average body mass index was 31.1 kg/m2. DPN was diagnosed based on a combination of reduced vibration perception measured by neurothesiometer and/or reduced light touch perception evaluated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 44 publications
2
39
2
3
Order By: Relevance
“…Of interest is that this group had the highest mean HbA1c suggesting that peripheral nerve function is more susceptible to uncontrolled diabetes but may be also exacerbated by the type of footwear most often worn in the Middle East, where wearing open toes sandals can lead to foot deformity and loss of microvascular flow to the foot [53]. DPN is also associated with autonomic nervous system dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest is that this group had the highest mean HbA1c suggesting that peripheral nerve function is more susceptible to uncontrolled diabetes but may be also exacerbated by the type of footwear most often worn in the Middle East, where wearing open toes sandals can lead to foot deformity and loss of microvascular flow to the foot [53]. DPN is also associated with autonomic nervous system dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, TNF-a regulated CRP which could recognize and activate the substances that influenced inflammatory response and defense mechanisms, resulting in reduction of blood supply, ischemia, or necrosis in nerve tissue and nerve impulse conduction block, as well as emergence of various nerve damage symptoms. Wang et al found that levels of CRP were significantly associated with higher odds of DPN [28]. Interestingly, CRP could induce expression of PAI-1 messenger RNA and promote generation of PAI-1 [29].…”
Section: Discussionmentioning
confidence: 99%
“…Embora não seja um fator de risco modificável, a duração do diabetes é de grande importância para a identificação e gerenciamento precoce de qualquer alteração na sensibilidade tátil e neuropatia 14 . O tempo de diagnóstico da doença, associado ao descontrole metabólico (HbA1c > 7%), traz graves consequências ao paciente portador de DM.…”
Section: Discussionunclassified
“…Ademais, a hemoglobina glicosilada alta é considerada um indicador para a gravidade da DM e a consequente alteração na sensação tátil, pois uma condição de hiperglicemia por longo prazo pode levar à diminuição do fluxo sanguíneo para os tecidos, provocando danos microvasculares nos nervos periféricos e, portanto, o desenvolvimento da neuropatia 14 .…”
Section: Discussionunclassified